Controllable Photoluminescence Behaviors of Amphiphilic Porphyrin Supramolecular Assembly Mediated by Cyclodextrins. Issue 24 (16th November 2017) - Liu, Guoxing; Zhang, Ying‐Ming; Xu, Xiufang; Zhang, Lu; Yu, Qilin; Zhao, Qian; Zhao, Chaoyue; Liu, Yu
Abstract: Tunable photoluminescence nanomaterials have aroused increasing interest from researchers recently due to their application in bioimaging, photodynamic therapy, and energy conversion. Herein, an artificial ternary nanosystem comprised of dithienylethene‐bridged bis(permethyl‐β‐CD)s, dodecyl‐bearing porphyrin, and amphipathic near‐infrared (NIR) cyanine fluorochrome is conveniently constructed by rationally designing the host/guest components, dimensions, and properties. In this system, an effective energy transfer (ET) from porphyrin to cyanine fluorochrome leads to the dramatic enhancement of NIR fluorescence intensity and more crucially, this process can be efficiently regulated by distinct light input, achieving photoswitching ET‐NIR fluorescence in aqueous media. Abstract : The energy transfer process from porphyrin to cyanine dye can be reversibly regulated via the photoisomerization of dithienylethene upon light irradiation, thus leading to the photoswitchable near‐infrared fluorescence emission in water. The present results provide a feasible supramolecular strategy in designing and constructing versatile light‐triggered fluorescence switches for potential application in the fields of biology and materials science.